2004
DOI: 10.1016/j.icesjms.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Stock structure of Sebastes mentella in the North Atlantic revealed by chemometry of the fatty acid profile in heart tissue

Abstract: Chemometric analysis of fatty acid profile in the heart tissue of redfish (Sebastes mentella, Travin 1951) from 11 locations in the waters off Norway, Faroe Islands, Iceland, and from two strata at different depths in the Irminger Sea revealed the presence of four separate stocks in the North Atlantic Ocean. The investigation has, statistically, shown: (i) a clear distinction between S. mentella on the Faroe Plateau and S. mentella in the deeps south-west of the Faroe Bank and on the Wyville Thomson Ridge; (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Our results showed a clear segregation of two gene pools of the pelagic S. mentella in the Irminger Sea and support earlier findings (for example, Johansen et al, 2000;Roques et al, 2002;Joensen and Grahl-Nielsen, 2004;Stefánsson et al, 2004. Bayesian-based methods (Supplementary Appendix S5, see Supplementary material and Table 1) were supported by the more traditional approaches such as the pairwise comparison plotted in Figure 4.…”
Section: Genetic Differentiationsupporting
confidence: 92%
“…Our results showed a clear segregation of two gene pools of the pelagic S. mentella in the Irminger Sea and support earlier findings (for example, Johansen et al, 2000;Roques et al, 2002;Joensen and Grahl-Nielsen, 2004;Stefánsson et al, 2004. Bayesian-based methods (Supplementary Appendix S5, see Supplementary material and Table 1) were supported by the more traditional approaches such as the pairwise comparison plotted in Figure 4.…”
Section: Genetic Differentiationsupporting
confidence: 92%
“…Regarding chemical analyses, a pilot study of using Cs-137 as a population marker indicated a closer relationship of redfish from Faroese waters to samples from the Barents Sea than to Icelandic samples. This was partly confirmed by fatty acid analyses of Joensen and Grahl-Nielsen (2002), dividing the occurrences of S. mentella around the Faroe Islands into one group related with the Icelandic shelf and another group connected to the Norwegian coast. Within the Irminger Sea, however, they reported considerable heterogeneity.…”
Section: Introductionmentioning
confidence: 70%
“…A pilot study of , using Cs-137 as population marker, indicated a closer relationship of redfish from Faroese waters to samples from the Barents Sea than to Icelandic samples. Fatty acid analyses of Joensen and Grahl-Nielsen (2004) separate the occurrences of S. mentella around the Faroe Islands into one group related with fish from the southeastern Icelandic shelf and deeper parts of the northeastern Irminger Sea from another group connected to the Norwegian coast.…”
Section: Discussionmentioning
confidence: 99%